Accounting for the Horsemen of the Administrative Apocalypse. (4th March 2019) - Fennimore, Anne; Sementelli, Arthur
Abstract : Administrators exhibiting dark personalities challenge arguments for accountability, particularly those reliant on technical rationality or an internal ethos. During periods of rapid change, organizations remain exposed to abuses of power potentially culminating in an administrative apocalypse. The dark tetrad of narcissists, Machiavellians, everyday sadists, and subclinical psychopaths serve as the harbingers of destruction in the face of limited accountability. Each tetrad member employs a unique self-serving, manipulative strategy that undermines public trust and intensifies the need for research on identifying and managing malevolent personalities in the public sector. The biblical images of the four horsemen of the apocalypse help contextualize the impacts on public administration.